The Implementation of English Literature in Classroom Literacy Learning in The Digital Era at MAN 2 Surakarta - Shofia, Arina Nuriyana; Sujito, Sujito (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Literature is the written language representing human expression or spoken works that are inspired by ideas, beliefs, experiences, and emotions in the form of imagination, reflection of reality or raw data wrapped in an aesthetic package through language. While literacy is the ability to read and write. The method used in this study is a qualitative method that uses descriptive analysis of data from interviews, discussions and observations and a literature review approach, while the references used are several scientific journals / articles, books and references from reliable sources. The subject of this research is the work of grade X and XI students or Phases E and F in the Independent Curriculum. The result showed of the understanding and provide into how the implementation of English literature can develop in the era of digitalization through literacy learning in the classroom such as the development of English literature in the era of digital technology that allows English literature to be recognized by students. The limitation of this research itself is that sources have the same perspective as the topic under study, so that this research can take and see from the perspective of the source, but with different content but the same context. So, with the role of English literature in learning literacy in the digital era, it certainly has a significant influence or contribution to the development of English literature. Thus, we can see that English literature can contribute or have a positive nuance to developments in literacy learning in the digital era, both theoretically and practically.